War, Coups & Terror : Pakistan's Army in Years of Turmoil - Cloughley, Brian (Barnsley Pen & Sword Military, 2008)
An insider with links to Pakistan's past and present military officers, Cloughley provides a unique insight into their Army's influence and position as a force in the fight against al-Qaeda and the Taliban.
Include Maps, Pictures and Index
Keywords: Pakistan. -- Army -- History. -- Pakistan -- Politics and government